Hubungan Persepsi Anak Terhadap Peran Ibu dengan Tingkat Cemas Saat Menstruasi Pertama (Menarche) Pada Pelajar Kelas VII SMPN 1 Simpang Kiri Subulussalam Tahun 2016 - Syelza Sisilia; Syahrul .; Taqwallah . (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2017)
The important occurrence that will happen to the girl who will hit puberty is menarche (first stage of menstruation), normally menstruation will start from young age to adult during her lifetime. Menstruation that often experienced by adult woman surely not a big problem. But it is a problem to a young woman, especially when it’s first menstruation they ever had. Not often for a young women who are not ready yet become anxious and stressed. Many things that caused the fear , one of them is Mother’s role to educate her daughter about menstruation. Education that given by her mother affects her daughter knowledge about menstruation, it could be misunderstood, probably menstruation known as a disease or a wound when the first time her daughter experienced it. This research intend to discover either there’s relation, children’s perception of mother’s role about menstruation with anxiety level on menarche. Research’s design is observasional analysis with cross-sectional matching. Sampling methods taken with total sampling of 57 respondents. Data collection held on 18th July 2016 in SMPN1 Simpang Kiri, Subulussalam. Using a questioner that designed by the researcher and has ben validated, lists in 10 questions and using also HARS scale modification. Collection data technique done by distribute the questioner and leading interview using HARS scale modification to measure the relation between children’s perception of mother’s role and anxiety during menarche. The result of data analysis using chi-square test found p-value 0,002, then p-value0,05 . This result shows us that there is a relation between children’s perception of mother’s role and anxiety level during menarche for 7th grade student in SMPN 1 Simpang Kiri Subulussalam on 2016